2012
DOI: 10.1007/s00125-012-2469-5
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q10 prevents GDP-sensitive mitochondrial uncoupling, glomerular hyperfiltration and proteinuria in kidneys from db/db mice as a model of type 2 diabetes

Abstract: Aims/hypothesis Increased oxygen consumption results in kidney tissue hypoxia, which is proposed to contribute to the development of diabetic nephropathy. Oxidative stress causes increased oxygen consumption in type 1 diabetic kidneys, partly mediated by uncoupling protein-2 (UCP-2)-induced mitochondrial uncoupling. The present study investigates the role of UCP-2 and oxidative stress in mitochondrial oxygen consumption and kidney function in db/db mice as a model of type 2 diabetes. Methods Mitochondrial oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
84
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(95 citation statements)
references
References 50 publications
10
84
1
Order By: Relevance
“…The present study demonstrates, using a non-invasive imaging method that only requires an intravenous injection of the tracer, a novel link between oxidative stress and pseudohypoxia in the diabetic kidney. This provides an additional mechanistic explanation for the beneficial effects of antioxidant treatment on diabetic kidney function (14,17).…”
Section: Discussionmentioning
confidence: 92%
“…The present study demonstrates, using a non-invasive imaging method that only requires an intravenous injection of the tracer, a novel link between oxidative stress and pseudohypoxia in the diabetic kidney. This provides an additional mechanistic explanation for the beneficial effects of antioxidant treatment on diabetic kidney function (14,17).…”
Section: Discussionmentioning
confidence: 92%
“…Mitochondrial uncoupling through UCP-2 is activated by oxidative stress, 13,14 and we have previously reported markedly increased UCP-2 activity in the diabetic kidney, resulting in increased mitochondrial QO 2 . 15,16 Preventing increased uncoupled QO 2 , therefore, seems feasible to minimize oxygen wasting in the diabetic kidney.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria was isolated from kidney cortex, and mitochondrial oxygen consumption was recorded using high-resolution respirometry using an Oroboros O2K (Oroboros Instruments, Innsbruck, Austria) and corrected for protein concentration. 15 Mitochondria function was determined as state 4 respiration in the presence of glutamate (10 mmol/L), state 3 respiration after the addition of 400 mmol/L ADP, and respiratory control ration calculated as state 3 over state 4 respiration. Mitochondrial uncoupling was determined as leak respiration (i.e., respiration in the presence of ATP-synthase inhibitor oligomycin [12 mg/mg protein]), and responsible mechanisms were evaluated as the sensitivity of leak respiration to guanosine diphosphate (GDP; 500 mmol/L; inhibitor of UCP) and carboxyatractylate (CAT; 0.5 mmol/L; inhibitor of ANT).…”
Section: Mitochondria Isolation and Functional Analysismentioning
confidence: 99%
“…Therefore, the other three statins are thought to more strongly inhibit the production of CoQ10 in extrahepatic cells than pravastatin. Recent basic studies have clearly shown that CoQ10 treatment prevents the development of DKD by reducing oxidative stress in db/db mice employed as a model of type 2 diabetes 21,22) . In light of these findings, the superiority of pravastatin demonstrated in the present study may be partly explained by differences in CoQ10 production in extrahepatic cells as a result of differences in lipophilicity.…”
Section: Comparison Of Risk Factors For the Incidence Of The Secondarmentioning
confidence: 99%